BRISE-plandok: a German legal corpus of building regulations. - Recski, Gábor; Iklódi, Eszter; Lellmann, Björn; Kovács, Ádám; Hanbury, Allan (Language Resources & Evaluation, 2025)
We present the BRISE-Plandok corpus, a collection of 250 text documents with a total of over 7000 sentences from the Zoning Map of the City of Vienna, annotated manually with formal representations of the rules they convey. The generic rule format used by the corpus enables automated compliance checking of building plans, a process developed as part of the BRISE (https://smartcity.wien.gv.at/en/brise/) project. The format also allows for conversion to multiple logic formalisms, including dyadic deontic logic, enabling automated reasoning. Annotation guidelines were developed in collaboration with experts of the city's building inspection office, describing nearly 100 domain-specific attributes with examples. Each document was annotated independently by two trained annotators and subsequently reviewed by the authors. A rule-based system for the automatic extraction of rules from text was developed and used in the annotation process to provide suggestions. The reviewed dataset was also used to train a set of baseline machine learning models for the task of attribute extraction, the main step in the rule extraction process. Both the rule-based system and the ML baselines are evaluated on the annotated dataset and released as open-source software. We also describe and release the framework used for generating and parsing the interactive xlsx spreadsheets used by annotators.